The possibility of manufacturing bricks from Quaternary Deposits from Al-Muthanna Governorate/ southern Iraq - Al-Hazaa, Sawsan Hameed; Shaker, Shereen Faroq (Iraqi Journal of Science, 2021)
This study is concerned with the identification of the validity of the Recent sediments deposited in the Playa for the purpose of making the laboratory bricks by extrusion and pressing. The steps followed in this study included the formation and then burning of the pyramids at (950-1100) C° for one hour of maturity to determine their applicability to the brick industry. The study area is located in Al Muthanna province, south of Iraq. It is located south of the district of Samawah at a distance of 80 km and to the north-west of Salman district, 64 kilometers south of Baghdad, represented by three hosts: (DHS 1, DH2 and S). The results of the chemical analysis of the study samples showed that they consist of the following major oxides: SiO2 = (39.34-42.82) TiO2 = (0.52-0.76) Na2O3 = (0.97-1.22) Fe2O3 = (4.19-5.89) CaO = (14.78-19.4) K2O = (0.91-1.14) Al2O3 = (8.02-9.85) MgO = (3.85-5.95) L.O.I = (16.31-19.32) silica SiO2 represented the highest ratio followed by Al2O3. Was manufactured 36 samples of the laboratory were manufactured and prepared by extrusion method were measured in dimensions (7 * 3.5 * 2.5) cm by extruding method and were burned at (950-1100) C° for the purpose of conducting physical and mechanical checks on them including Linear and volume shrinkage, color, Water absorption, Efforescence, and compressive strength. The results of these tests showed a decrease in water absorption and Efforescence, a decrease in the values of compressive strength with increased burning temperature, decreased Linearand volume shrinkage in most samples and increased in other samples with increasing burning temperature. In addition, 12 samples were made of the cylindrical laboratory size (diameter 50 mm, height 60 mm) in semi-dry pressing method, and were burned at (950-1100) C° for the purpose of physical and mechanical tests, color, Water absorption, Efforescence, and compressive strength. The results of these tests showed a decrease in water absorption and Efforescence and an increase in the values of compressive resistance while increasing the temperature of burning, while the colors of the samples ranged from light brown and yellow or pale yellow to white. The results of physical assays were met Linear and volume shrinkage, color, Water absorption and Efforescence. As well as mechanical tests: compressive strength results were in accordance with the Iraqi standard for this industry where the data of the results of this study showed the validity of these samples for the industry mentioned above.